Coleopteran Antimicrobial Peptides: Prospects for Clinical Applications - Monde Ntwasa; Akira Goto; Shoichiro Kurata (International Journal of Microbiology)
Antimicrobial peptides (AMPs) are activated in response to septic injury and have important roles in vertebrate and invertebrate immune systems. AMPs act directly against pathogens and have both wound healing and antitumor activities. Although coleopterans comprise the largest and most diverse order of eukaryotes and occupy an earlier branch than Drosophila in the holometabolous lineage of insects, their immune system has not been studied extensively. Initial research reports, however, indicate that coleopterans possess unique immune response mechanisms, and studies of these novel mechanisms may help to further elucidate innate immunity. Recently, the complete genome sequence of Tribolium was published, boosting research on coleopteran immunity and leading to the identification of Tribolium AMPs that are shared by Drosophila and mammals, as well as other AMPs that are unique. AMPs have potential applicability in the development of vaccines. Here, we review coleopteran AMPs, their potential impact on clinical medicine, and the molecular basis of immune defense.